‘Is the library open?’: Correlating unaffiliated access to academic libraries with open access support - Wilson, Katie; Neylon, Cameron; Brookes-Kenworthy, Chloe; Hosking, Richard; Huang, Chun-Kai (Karl); Montgomery, Lucy; Ozaygen, Alkim (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
In the context of a growing international focus on open access publishing options and mandates, this paper explores the extent to which the ideals of ‘openness’ are also being applied to physical knowledge resources and research spaces. This study, which forms part of the larger Curtin Open Knowledge Initiative project, investigates the relationship between academic library access policies and institutional positions on open access or open science publishing. Analysis of library access policies and related documents from twenty academic institutions in Asia, Australia, Europe, North America, Africa and the United Kingdom shows that physical access to libraries for members of the public who are not affiliated with a university is often the most restricted category of access. Many libraries impose financial and sometimes security barriers on entry to buildings, limiting access to collections in print and other non-digital formats. The limits placed on physical access to libraries contrast strongly with the central role that these institutions play in facilitating open access in digital form for research outputs through institutional repositories and open access publishing policies. We compared library access policies and practices with open access publishing and research sharing policies for the same institutions and found limited correlation between both sets of policies. Comparing the two assessments using Spearman’s rank correlation coefficient confirmed open access policies have a direct association with the narrow aspects of public access provided through online availability of formal publications, but are not necessarily associated (in the universities in this study) with delivering on a broader commitment to public access to knowledge. The results suggest that while institutional mission statements and academic library policies may refer to sharing of knowledge and research and community collaboration, multiple layers of library user categories, levels of privilege and fees charged can inhibit the realisation of these goals. As open access publishing options and mandates expand, physical entry to academic libraries and access to print and electronic resources has contracted. This varies within and across countries, but it conflicts with global library and information commitments to open access to knowledge.